Weldability between steel type 304H and steel type P91 for high temperature applications - Krstevska, Aleksandra; Poser B. Maja; Zdraveski, Filip (Serbian Welding Society, 2023)
This paper presents research about weldability between two dissimilar steels, martensitic steel P91 and 304H austenitic steel. Both materials are being preferred as a structural material for higher temperature applications due to their good mechanical properties at high temperatures. The mechanical properties at high temperature, such as tensile strength and creep resistance, are very important factors that ensure the application of materials. The P91 is modified martensitic Cr steel with higher amount of chromium which improves the higher temperature strength and molybdenum that increases creep resistance. On the other hand, the 304H represents advance austenitic stainless steel with controlled carbon content, which makes it ideal for applications requiring good mechanical properties at elevated temperatures. With increasing the demand of high efficiency in the power generation industry the high temperature applications usually require joints between advanced austenitic stainless steels and new class martensitic stainless steels in order to achieve the goal with the increased steam parameters. Therefore, this paper focuses on the weldability assessment between these two different steels and the characteristics of the weld metal.
Keywords: P91; 304H; weldability; dissimilar weld joint